Integrating Technology for Multimodal Literacy in English Studies - Dada, Charisa (NIU Journal of Humanities; Vol. 10 Núm. 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
Multimodal literacy is being literate in all forms of literacy surrounding learning and representing meaning, including multimedia and digital interactions. It involves the use of diverse communication modes - visual, audio, and spatial, alongside traditional reading and writing in education. The aim of this paper is to investigate how technology aids the development of multimodal literacy in English studies students. Three universities in south-south Nigeria, Edo state, were used as case studies. Qualitative research methods were employed, including semi structured interview, student focus group and classroom observations. The theoretical frameworks of the New London Group, Technological Pedagogical Content Knowledge (TPACK), and Constructivist Learning Theory were applied in this paper. Findings reveal that being technologically literate facilitates multimodal literacy as it enhances knowledge sharing, caters for different learning styles and helps students synthesise information across multiple modes of representation. However, challenges such as digital literacy gaps, financial constraints, resistance to change on the part of instructors, and concerns about curriculum modification, assessment, and academic integrity hinder effective implementation. The paper concludes that integrating technology for multimodal literacy offers significant opportunities for a more dynamic, inclusive, and flexible learning and recommends continuous training for instructors, continued investment in infrastructure, multimodal literacy training, and collaborative curriculum development to fully realise the potential of multimodal literacy. The findings contribute to the growing body of research on the integration of technology for multimodal literacy development. Keywords: Multimodal Literacy, Technology Integration, Higher Education, English Studies